Birth weight and childhood growth in daughters of women with irregular menstrual cycles. (June 2013) - Wang, Erica T.; Cirillo, Piera M.; Kao, Chia-Ning; Cohn, Barbara A.; Cedars, Marcelle I.
Abstract Menstrual irregularity has been associated with insulin resistance, type 2 diabetes mellitus and markers of metabolic dysfunction. This study aimed to determine whether irregular menstrual cycles (MCs) in reproductive-age women are associated with the weight of their daughters at birth and growth up to age five. We studied 4863 pregnant women with menstrual history data in a prospective cohort, recruited from the Kaiser Health Plan (1959–1966). Serial measures of their daughters' weight and height were abstracted from medical records. We used analysis of covariance, stratified by maternal body mass index, to explore the association between maternal MC and infant birth weight (BW). We included 4774 daughters in a repeated measures analysis to compare the effect of maternal MC on childhood weight through age five. Daughters of non-obese women with irregular MC had a statistically significant lower BW compared to daughters of women with regular MC; this difference was notably amplified among obese women. The daughters' weights were not statistically different when growth was assessed from birth to five years. We conclude that daughters of obese women with irregular MC, in particular, had significantly lower BW compared to daughters of women with regular MC, which did not persist over five years of follow-up.